If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 4) = 3x Reorder the terms: 7(4 + x) = 3x (4 * 7 + x * 7) = 3x (28 + 7x) = 3x Solving 28 + 7x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 28 + 7x + -3x = 3x + -3x Combine like terms: 7x + -3x = 4x 28 + 4x = 3x + -3x Combine like terms: 3x + -3x = 0 28 + 4x = 0 Add '-28' to each side of the equation. 28 + -28 + 4x = 0 + -28 Combine like terms: 28 + -28 = 0 0 + 4x = 0 + -28 4x = 0 + -28 Combine like terms: 0 + -28 = -28 4x = -28 Divide each side by '4'. x = -7 Simplifying x = -7
| 1+2x^4=x^2(x^2+3)+x^2-3 | | -6=6-6a+3a | | 11/7x-9=4/7x | | 100t-9.8t^2=0 | | 6=5x-4x | | 6x-8=10x-28 | | -2=4k-6k | | 11/4r-9=4/7r | | X=-9/67 | | 2/3(6x-x)=5/6x | | -8(1-6k)+5k=8k+37 | | x+4x-3x+1=3 | | 8x^4-56x^3+98x^2=0 | | 892=d+828 | | 2x+7-4(x+1)=3x+7 | | 5/7-5/14 | | 28108.16=z*a | | 2/3*-4=10 | | 14x+10-8x=24-x | | 588=14f | | 8x^4-56x^3+92x^2=0 | | X-3/8=9/8 | | -2(5x+5)=6x-10 | | 26+n=78 | | x-16500=11608.16 | | 8(1-6n)=-7n+8 | | ln(1-4x)=6x | | 3a+7a^2= | | x-y=11608.16 | | 6(1-6x)=39-3x | | 3y=18-6z | | 5m+5b=80 |